The contribution of B.M. Bim-Bad to the pedagogical normative reconstruction - Aura Hapenciuc (Association of Social and Educational Innovation, 2018)
The paper highlights the contribution of the contemporary educator of the eastern area B.M. BimBad in demonstrating the scientificity of pedagogy. Normative provides the ordering of facts, events, processes etc. The normativity pedagogical model proposed by .M. Bim-Bad includes: pedagogy axioms (fundamental truths that are well known) laws of pedagogy, specific laws, concrete laws, pedagogical principles, pedagogical rules. Axiomatic system will be essential in contemporary postmodern pedagogy, especially in the field of general theories (foundations pedagogy / general theory of education, general teaching / general theory of training), serving to improve and develop them continuously. The research contains the concepts, principles and axioms used by Russian pedagogues, through which we strive to demonstrate the impact of Russian pedagogy on the epistemic development of education science and its contribution to world heritage.